Do the Liability convention 1992 and the fund conventions covering all kinds of damage result due to oil spills from the legal aspects of marine oil pollution liabilities? - Yassine, Karim (2023)
Marine oil pollution incidents represent a pressing global environmental concern, necessitating robust international legal frameworks for addressing liability and compensation. This thesis critically examines the adequacy and comprehensiveness of the CLC 1969, Liability Convention of 1992 and the Fund Conventions in addressing all types of damage transpiring from oil spills. The study employs a multifaceted legal analysis, encompassing the conventions provisions, case law, and international jurisprudence. Also, this paper objective is to examine whether the Liability Convention 1992 and the Fund Conventions cover all types of damage resulting from oil spills, ranging from environmental damage to economic losses, with an emphasis on the examination of legal aspects. The research commences with a particular examination of the historical context, emergence, and evolution of these conventions. This exploration explicates the underlying principles and objectives that guided their formulation. The ensuing sections explore into a comprehensive assessment of the conventions' provisions, analysing their capacity to encompass diverse categories of damage, including environmental and economic aspects. Key areas of inquiry including the possibility of liability, the definition of damage, and the adequacy of compensation mechanisms. Through meticulous legal interpretation and comparative analysis, the study discerns the conventions' strengths and limitations in offering compensation to various parties and sectors affected by oil spills. To complement the analysis, this research incorporates an experiential dimension by assessing the conventions' practical application in selected case studies of notable oil spill incidents. By contrasting legal guidelines with real-world outcomes, the study offers insights into the conventions' effectiveness in addressing the myriad dimensions of marine oil pollution liabilities. Furthermore, the research contemplates potential reforms or enhancements to the existing legal framework to address emerging challenges in the framework of marine oil pollution. It engages with contemporary progresses in international environmental law and policy, including the incorporation of a broader spectrum of environmental damage and the evolving responsibilities of various parties in preventing and mitigating oil spills. Ultimately, this thesis endeavours to contribute to the ongoing discourse on international legal frameworks for marine oil pollution liabilities. By critically evaluating the Liability Convention of 1992 and the Fund Conventions, it seeks to illuminate opportunities for legal refinement and adaptation to ensure comprehensive coverage of all forms of damage resulting. from oil spills, thereby advancing the imperative of environmental protection and justice on a global scale.